Latin written sources and Greek archaeological evidence: the Inousses Islands as a case history - Andrea Nanetti (2016)
Methone, Korone and the Inousses Islands were a strategical node for sailing between Western and Eastern Mediterranean regions. They were the only settlements of the Peloponnese directly ruled by the Most Serene Republic of Venice from 1205–1206 until 1500. They can be a case history in leading a sinergical interpretation of archaeological records with archival documents, chronicles, diares of travellers and engravings in order to individuate the Venetian cultural phase of already Byzantine settlements as a way of interethnical and intercultural relationship in their history.